2019
DOI: 10.1097/ijg.0000000000001332
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of Bruch Membrane Opening Morphometry in Myopic Glaucoma

Abstract: Précis: The Bruch membrane opening (BMO) was posteriorly bowed and the degree of nonplanarity increased in stable and progressive glaucoma subjects. BMO became more posterior relative to the Bruch membrane (BM) in control and both stable and progressive glaucoma subjects. Purpose: To investigate longitudinal changes in morphologic characteristics of the BMO in control and glaucomatous subjects. Materials and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Using SS-OCT, we have previously published on the morphological characteristics of the ONH and peripapillary region in myopic normal and glaucomatous subjects. [24][25][26] We showed that axial length was a significant factor in the shape of Bruch's membrane opening (BMO) and the degree of posterior bowing of the peripapillary BM. In the present study, we extend the investigation to the prelaminar neural canal between BMO and ALI and anterior lamina cribrosa morphology in healthy and glaucomatous myopic subjects to further examine the structural effects of myopia and glaucoma in the ONH.…”
Section: Introductionmentioning
confidence: 99%
“…Using SS-OCT, we have previously published on the morphological characteristics of the ONH and peripapillary region in myopic normal and glaucomatous subjects. [24][25][26] We showed that axial length was a significant factor in the shape of Bruch's membrane opening (BMO) and the degree of posterior bowing of the peripapillary BM. In the present study, we extend the investigation to the prelaminar neural canal between BMO and ALI and anterior lamina cribrosa morphology in healthy and glaucomatous myopic subjects to further examine the structural effects of myopia and glaucoma in the ONH.…”
Section: Introductionmentioning
confidence: 99%
“…Using SS-OCT, we have previously published on the morphologic characteristics of the ONH and peripapillary region in myopic normal and glaucomatous subjects. [24][25][26] We showed that axial length was a significant factor in the shape of Bruch's membrane opening (BMO) and the degree of posterior bowing of the peripapillary BM. In the present retrospective pilot study, we extend the investigation to the prelaminar neural canal between BMO and ALI and anterior lamina cribrosa morphology in healthy and glaucomatous myopic subjects to further examine the structural effects of axial length and glaucoma in the ONH.…”
mentioning
confidence: 99%
“…Compared with a conventional spectral domain OCT, a swept-source OCT (SS-OCT) with a 1060-nm wavelength source allows for visualization of deeper structures in the ONH. Using SS-OCT, we have previously published on the morphologic characteristics of the ONH and peripapillary region in myopic normal and glaucomatous subjects 24–26. We showed that axial length was a significant factor in the shape of Bruch’s membrane opening (BMO) and the degree of posterior bowing of the peripapillary BM.…”
mentioning
confidence: 99%